Pulsatility hemodynamics during speed modulation of continuous‐flow total artificial heart in a chronic in vivo model. Issue 8 (31st March 2022) - Kuroda, Taiyo; Miyamoto, Takuma; Miyagi, Chihiro; Polakowski, Anthony R.; Flick, Christine R.; Kuban, Barry D.; Voros, George B.; Such, Kimberly; Fukamachi, Kiyotaka; Karimov, Jamshid H.
Abstract: Background: The evaluation of pulsatile flow created by the new Cleveland Clinic continuous‐flow total artificial heart (CFTAH100), which has a re‐designed right impeller and motor, had not been tested in vivo. The purpose of this study was to evaluate the feasibility of pulsatility with the CFTAH100 during the application of pump speed modulation protocols in a chronic animal model. Methods: A 30‐day chronic animal experiment was conducted with a calf. Five pulsatile studies were performed on the alert animal. The mean pump speed was set at 2800 rpm, and modulated sinusoidally within a range of 0 to ± 35% of mean speed, in increments of 5% at 80 beats per minute (bpm). The pressures and pump flow were collected and a pulsatility index (PI) was calculated. Results: The calf was supported with the CFTAH100 without any major complications. The maximum and minimum pump flows changed significantly from baseline in all conditions, while the mean pump flow did not change. All flow pulsatility (FP) readings in all conditions significantly increased from baseline, and the percent modulation (%S) and FP had a strong positive correlation ( r = 0.99, p < 0.01). The PI also increased significantly in all conditions (maximum at %S of 35%, 2.2 ± 0.05, p < 0.01), and a positive correlation between %S and PI ( r = 0.99, p < 0.01) was observed. Conclusion: The CFTAH100 showed the feasibility of creating pulsatile circulation with sinusoidal pump speed modulation. Abstract : The pulsatile circulation created with the Cleveland Clinic Total Artificial Heart was evaluated in a 30‐day chronic in vivo experiment. The pump demonstrated the feasibility of creating pulsatile circulation.